The role of crop diversification in improving household food security in central Malawi - Nelson Mango; Clifton Makate; Lawrence Mapemba; Mathinda Sopo (Agriculture & Food Security, 2018)
Abstract Background This paper concerns the role of crop diversification in improving household food security in central Malawi. In this country, the agricultural sector is dominated by smallholder farming and rain-fed food production systems that are facing increasing challenges from land degradation and declining soil fertility. Maize is the staple food crop, and as such, the majority of farmers grow it regardless of land suitability. This has led to what scientists have labeled as “maize poverty trap.” In the event of prolonged drought, maize fails thus leaving farmers food insecure. However, research in Sub-Saharan Africa has shown that crop diversification provides smallholder farmers with a diversity of diet, improves their income, and nutrition security. Due to increased cases of malnutrition and food insecurity, in the wake of climate change, government of Malawi has in the past few years intensified extension efforts for crop diversification. Methods The study is based on a sample of 271 randomly selected smallholder farming households from central Malawi. It investigates the influence of crop diversification and other household socioeconomic characteristics on the household Food Consumption Score and Household Food Insecurity Access Score. In our analysis, we rely heavily on a combination of ordinary least squares techniques and some descriptive statistics. Results Our results show that crop diversification, cattle ownership, access to credit and attaining of education have a positive and significant effect on the household Food Consumption Score. Precisely, crop diversification, cattle ownership and access to credit are all significant at 5% level, while education is significant at 10%. In addition, crop diversification and attaining of formal education by household head were found to have a negative and significant effect on Household Food Insecurity Access Score and were all significant at 1% level. Conclusion and policy recommendation Based on our study findings, we conclude that crop diversification is one viable option in smallholder farming that can ensure establishment of resilient agricultural systems that can contribute significantly to household food security. In terms of policy, the results imply that the current efforts by government of Malawi to intensify promotion of crop diversification should remain a priority policy direction due to the continued malnutrition and food insecurity threat. This is particularly so in this era of climate variability that poses an extra burden to farmers.